Final report of the SIM.QM-S8 supplementary comparison, trace metals in drinking water - Yang, Lu; Nadeau, Kenny; Pihillagawa, Indu Gedara; Meija, Juris; Mester, Zoltan; Napoli, Romina; Pérez Zambra, Ramiro; Ferreira, Elizabeth; Forigua, Diego Alejandro Ahumada; Gamba, Johanna Paola Abella (IOP Publishing, 2018)
After completing a supplementary comparison SIM.QM-S7, the National Metrology Institute of Colombia (NMIC) requested to National Research Council of Canada (NRC) a subsequent bilateral comparison, because INMC considered that its results in SIM.QM-S7 unrepresentative of its standards. In this context, NRC agreed to coordinate this bilateral comparison with the aim of demonstrating the measurement capabilities of trace elements in fresh water. Participants included NMIC and LATU. No measurement method was prescribed by the coordinating laboratory. Therefore, NMIs used measurement methods of their choice. However, the majority of NMIs/DIs used ICP-MS. This SIM.QM-S8 Supplementary Comparison provides NMIs with the needed evidence for CMC claims for trace elements in fresh waters and similar matrices. Main text To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/. The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).